Teoria da atividade e modelos de leitura em livros didáticos de Português – L2 - Pinto, Cândida Martins; Richter, Marcos Gustavo (Linguagens & Cidadania, 2017)
Nowadays, considering the process of a foreign language or second language acquisition, a big importance is given to the previous knowledge of the learner: top-down model. As the same rule, bottom-up model, involving formal and grammatical aspects, has its relevance in a second stage of the learning. A mature learner is that who is able to link these two models during the reading, using, thus, the interactive model. Considering this, this study aims to, in a first stage, discuss relevant questions for the use of the three models in language classes in general and in Portuguese for foreigner classes in particular, as well as the importance of them for a good reading. In a second stage, a Portuguese for foreigners textbook will be analyzed, according to Activity Theory, in order to verify when the models appear in reading tasks.